2009
DOI: 10.1002/pds.1887
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with medicine use among children aged under 12 years—a population survey in Finland

Abstract: A considerable proportion of children use prescription and OTC medicines in Finland. Young age and health-related factors, morbidity and health status, and parental medicine use predicted children's medicine use. Further studies are needed to examine the association between parents' and children's medicine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
44
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 20 publications
10
44
2
3
Order By: Relevance
“…Two studies found no influence of parental socioeconomic status. 4,17 Our findings concur with recent research indicating that parents' own health and medicating behavior influence the self-medication of their children.…”
Section: Relation To Previous Studiessupporting
confidence: 82%
See 3 more Smart Citations
“…Two studies found no influence of parental socioeconomic status. 4,17 Our findings concur with recent research indicating that parents' own health and medicating behavior influence the self-medication of their children.…”
Section: Relation To Previous Studiessupporting
confidence: 82%
“…However, our results are in accordance with previous studies showing an association between maternal and child self-medication with OTC medications. 17,20,28 We did not detect any influence of socioeconomic factors, as suggested by earlier studies, perhaps due to our limited study population. In 2003, Tobi et al 15 found a high parental education level to be associated with increased child OTC drug use.…”
Section: Relation To Previous Studiessupporting
confidence: 54%
See 2 more Smart Citations
“…Students' perspectives on medicines and their use, was similar to that seen in previous studies in Finland [26,27,30]. Fourth graders' perspectives included the view that as well as the benefits, medication always includes risks such as the side effects.…”
Section: Discussionmentioning
confidence: 53%